Pengembangan Booklet LKPD untuk Meningkatkan Kemampuan Berbicara Siswa Kelas IV Sekolah Dasar - Reni Reni; Hajar Nurul Izzati; Muhammad Ikhsan; Rifqa Gusmida Syahrun Barokah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research is motivated by the low speaking ability of elementary school students which is characterized by a lack of confidence, difficulty in expressing opinions in a coherent manner, and the lack of students' ability to express information clearly in learning Indonesian. These problems show that the learning that takes place has not fully provided opportunities for students to actively practice speaking skills. This research aims to Develop a booklet based on Student Worksheets (LKPD) on interview text materials to support the speaking skills of grade IV elementary school students. The method used is research and Development with a 4D model which includes the define, design, and Develop stages. At the Development stage, the product is validated by media experts and subject matter experts to assess the feasibility level of the LKPD booklet Developed. The results of the study showed that the LKPD booklet obtained a feasibility percentage of 91.17% in the media aspect and 90.32% in the material aspect with a very feasible category. These results show that the LKPD booklet Developed has met the eligibility criteria both in terms of appearance and content as teaching materials for learning Indonesian language in elementary schools. However, this research is still limited to the product validation stage, so further research is needed through field trials to determine the effectiveness of LKPD booklet s in improving students' speaking skills in more depth.